Numerical investigation for effects of natural light and ventilation on 3D tomato body heat distribution in a Venlo greenhouse - Yu, Guanghui; Zhang, Shanhong; Li, Shuai; Zhang, Minshu; Benli, Huseyin; Wang, Yang (Elsevier, 2023)
Maintaining suitable temperature level around tomato in the greenhouse is essential for the high-quality production. However, in summer, the temperature level around the tomato is usually unclear except using a high-precision temperature imager. To solve this problem, thermal performance of 3D (three-dimensional) tomato model built based on SolidWorks was investigated by the computational fluid dynamics (CFD) simulations. To assess the effect of temperature distribution around the tomato, a simplified 3D tomato numerical model was firstly validated by a set of field measurement data. The light intensity and indoor ventilation were regarded as the mainly environment factors in the Venlo greenhouse, thermal stratification around tomatoes at different time of day was further studied. The numerical results illustrated the different temperature distribution around tomato body under different radiation intensity. It was found that ventilation could obviously adjust the temperature gradient around the tomato, and alleviate high temperature effect particularly in summer. Suitable ventilation could create a suitable thermal environment for the tomato growth. This study clearly demonstrated 3D temperature distribution around tomatoes, which is beneficial to provide the reference for accurate detection of 3D tomato temperature and appropriate thermal environment design. (c) 2022 China Agricultural University. Production and hosting by Elsevier B.V. on behalf of KeAi. This is an open access article under the CC BY-NC-ND license (http://creativecommons. org/licenses/by-nc-nd/4.0/).
Keywords: CFD; 3D Tomato body; Heat distribution; Greenhouse environment; Growth condition